2009
DOI: 10.1093/annonc/mdn774
|View full text |Cite
|
Sign up to set email alerts
|

Global Lung Oncology Branch trial 3 (GLOB3): final results of a randomised multinational phase III study alternating oral and i.v. vinorelbine plus cisplatin versus docetaxel plus cisplatin as first-line treatment of advanced non-small-cell lung cancer

Abstract: Both arms provided similar efficacy in terms of response, time-related parameters and QoL, with an acceptable tolerance profile. In the current Global Lung Oncology Branch trial 3, NVBo was shown to be effective as a substitute for the i.v. formulation. This can relieve the burden of the i.v. injection on day 8 and can optimise the hospital's resources and improve patient convenience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 31 publications
1
67
0
2
Order By: Relevance
“…Lastly, vinorelbine as a single agent with radiation therapy was well tolerated, and the response rate was approximately 60% 8 . In combination trials in nsclc, an acceptable safety and efficacy profile was observed with vinorelbine plus platinum-based chemotherapy, as well as with oral or intravenous formulations of vinorelbine alone, compared with platinum plus taxanes [9][10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, vinorelbine as a single agent with radiation therapy was well tolerated, and the response rate was approximately 60% 8 . In combination trials in nsclc, an acceptable safety and efficacy profile was observed with vinorelbine plus platinum-based chemotherapy, as well as with oral or intravenous formulations of vinorelbine alone, compared with platinum plus taxanes [9][10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…The cisplatin/vinorelbine doublet is a well studied and active doublet in the treatment of NSCLC either in the adjuvant [27,28] or in the advanced disease setting [29][30][31]. On the other hand, this combination is very toxic with severe neutropenia occurring in more than 40%-80% of the patients [27,29,31].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this combination is very toxic with severe neutropenia occurring in more than 40%-80% of the patients [27,29,31]. Thus, we considered of interest a study evaluating the combination of metronomic administration of vinorelbine with cisplatin, a strategy which is likely to have a more favorable toxicity profile.…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference by histology was observed in the efficacy of these regimens; however, overall, a survival advantage was observed for patients with scc compared with those with adenocarcinoma (p = 0.0021). In the phase iii Global Lung Oncology Branch trial 3, patients with advanced nsclc were treated with first-line vinorelbine-cisplatin or with docetaxel-cisplatin 61 . In patients with scc, median os was 9.8 months in the docetaxel arm and 8.9 months in the vinorelbine arm; the respective orrs were 28% and 25%.…”
Section: Taxanes and Histologymentioning
confidence: 99%